Disturbance observer-based saturated optimal super-twisting integral sliding mode midcourse guidance against maneuvering targets - Chen, Wenxue; Gao, Jiawei; Gao, Changsheng (Control engineering practice, 2025)
This work addresses the problem of calculating midcourse guidance command in ballistic missile defense techniques against a maneuvering target. An improved optimal sliding mode guidance scheme is proposed based on the optimal control and sliding mode control techniques, which consider zero-effort-miss (ZEM), energy consumption, input saturation, and autopilot lag dynamics. The guidance problem is formulated as a nonlinear, uncertain, weakly observable system and modified to describe the equivalent guidance model by introducing the virtual state variables. The proposed guidance scheme is only needed to design the lateral acceleration in the instantaneous rotation plane of LOS (IRPL) by offering the line-of-sight (LOS) rotation coordinate frame as the reference frame of the three-dimensional relative kinematic model. Besides, the minimization of a performance index is guaranteed by introducing the optimal control theory. This proposed guidance scheme incorporates a novel hybrid extended state observer (NHESO) to estimate the system’s unmeasured states and disturbances in an integrated manner. Afterward, an integral sliding mode guidance algorithm is elucidated to resist interferences by introducing the integral sliding mode control theory. Also, the super-twisting algorithm is presented as the reaching law to avoid the chattering problem. Finally, the superior performance of the designed midcourse guidance scheme is validated in contrast to existing guidance laws, particularly energy consumption and robustness. •This paper presents a novel SOSTISMG midcourse scheme.•The proposed observer evaluates the same in an integrated manner, which improves tracking accuracy and stability via designing a linear function.•The SOSTISMG midcourse guidance scheme is developed to consider energy consumption, zero-effort-miss constraints, input saturation, autopilot dynamics, and disturbances.